Corpo ex-posto : disparador de possibilidades na obra de Elisa Ohtake - Leite, Daniela Correa (2015)
What moves the actor/performer to create and re-create a body with vitality on the scene? This concern gave direction to the research, suggesting the existence of the body as something to be experienced, more than explained, the body while power generation in performative theater. To watch the show Take My Breath and False Entertainment, both directed by the artist Elisa Ohtake, Deleuze and Guattari were references, because they see the body as a becoming a becoming, something in the process. From the survey of literature and audiovisual material, thematic interviews with the director and two performers about their creative processes were performed. It could be observed , then, that the actor/performer may, in practice, try other possibilities, beyond any pre-established form and in that sense, blurring the boundaries between artistic languages, making theater an event, or rather a trigger experiences.